Quality improvement: The delivery of true early mobilisation in an intensive care unit - van Willigen, Zoe (BMJ Qual Improv Rep, 2016)
Early mobilisation initiatives within the critical care environment have been shown to improve outcomes for patients. Early mobilisation has been defined as occurring within the first two to five days of the intensive care stay, but in practice this can be difficult to deliver. We conducted a quality improvement (QI) project to deliver early mobilisation in a large general intensive care unit. Mechanically ventilated medical patients received an integrated package of care involving two additional daily sessions of mobility therapy, in combination with minimal sedation where possible. Prospective baseline data was collected from January to March 2012; the QI project commenced in April 2012. Improvement cycle 1 completed in March 2015 and improvement cycle 2 in March 2016. Results have suggested a reduction in time to first mobilisation for intensive care survivors from 16.3 days in 2012, to 4.3 days at the end of improvement cycle 2. This was associated with a decrease in mean intensive care length of stay from 20.8 days in 2012, to 11.2 days at the end of improvement cycle 2. This QI project enabled patients to mobilise out of bed within the first five days of their intensive care stay and to be discharged earlier from the ICU, on going analysis is required to verify these findings.